The Effect of Solvent Extraction of Light Lubricating Oil on Viscosity Index and Chemical Composition - A.-K. Mohammed, Abdul-Halim; K. Hussain, Hussain; J. Sadiq, Rafal (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
An investigation was conducted for the improvement of viscosity index of light lubricating oil fraction (40 stock)obtained from vacuum distillation unit of lube oil plant of Daura Refinery, using solvent extraction process.In this study furfural solvent was used to extract the undesirable materials which reduce the viscosity index of rawlubricating oil fraction.The studied effecting variables of extraction were extraction temperature range from 70 to 110°C, and solvent to oilratio range from 1:1 to 4:1 (wt/wt).The n-d-M method was used for calculation of carbon distribution and structural group analysis of the raffinateproduced from furfural extraction.Also the three component phase diagram for a mixed-base oil and furfural at different temperature was drawn.The results of this investigation show that the viscosity index of lubricating oil fraction increases with increasingextraction temperature and increasing the solvent to oil ratio and reaches 115.6 at extraction temperature 110°C andsolvent to oil ratio 4:1.Further more, the results show that the viscosity, refractive index, density, sulfur content and percentage yield ofproduced raffinate were decreased as the extraction temperature or solvent to oil ratio increases for extraction process.